2014
DOI: 10.1371/journal.pone.0086486
|View full text |Cite
|
Sign up to set email alerts
|

Small Activating RNA Restores the Activity of the Tumor Suppressor HIC-1 on Breast Cancer

Abstract: HIC-1 is a gene that is hypermethylated in cancer, and commonly downregulated in human breast cancer. However, the precise mechanisms and molecular pathways regulated by HIC-1 remain unclear. We assessed HIC-1 expression on a tissue microarray containing 80 cases of breast cancer. We also analyzed its biological function by restoring HIC-1 expression using 5-aza-2′ deoxycytidine (5-CdR) and small-activating RNAs for the reversal of HIC-1 tumor suppressive effects on MCF-7 and MDA-MB-231 cell lines. An Agilent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…ERBB2 is located in chromosome 17q21.2, where some common oncogenes or tumor suppressor genes, such as TOP2A, TAU, p53, and HIC-1 are located ( Zhang and Yu, 2011 ). Our previous studies confirmed that re-activation of tumor suppressor HIC-1 by small-activating RNAs inhibits cell division, growth and invasion ( Zhao et al, 2014 , 2015 ). Retinoic acid receptor alpha (RARA) is another gene located on chromosome 17q21.2.…”
Section: Introductionsupporting
confidence: 82%
“…ERBB2 is located in chromosome 17q21.2, where some common oncogenes or tumor suppressor genes, such as TOP2A, TAU, p53, and HIC-1 are located ( Zhang and Yu, 2011 ). Our previous studies confirmed that re-activation of tumor suppressor HIC-1 by small-activating RNAs inhibits cell division, growth and invasion ( Zhao et al, 2014 , 2015 ). Retinoic acid receptor alpha (RARA) is another gene located on chromosome 17q21.2.…”
Section: Introductionsupporting
confidence: 82%
“…dsHIC1-2998 was further confirmed as effective saRNA for gastric cancer and breast cancer cells. The saRNA-HIC-1 effectively activated the HIC-1 gene with evident suppression of cell growth and induction of apoptosis in breast cancer ( 14 ). In the current study, further evidence has been obtained, confirming that saRNA-HIC-1 effectively inhibits clonogenicity in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The dsRNA targeting the region (2998 bp) above from the transcription start site of human HIC-1 was designed based on the rational design rules described ( 9 , 15 ) and our previous reports ( 4 , 14 ). The sequences of saRNA-HIC-1 (dsHIC-1-2998) used in this experiment were as follows: Sense, 5′-CGGUUUCCMGGAGAAGUUATT-3′ and antisense, 5′-UAACUUCUCCAGGAAACCGTT-3′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The McF-7 cells were transfected as described above. At 24 h post-transfection, RNA was extracted using TRIzol (15596-018; Thermo Fisher Scientific, Inc.), purified using an RNeasy mini kit (74106; Qiagen GmbH), amplified and labeled using the low input quick amp labeling kit (5190-2305; Agilent Technologies, Inc.); each slide was then hybridized, scanned; and data were extracted, and normalized as previously described (12,17). Two samples were used for gene chip assay.…”
Section: Gene Chip Assaymentioning
confidence: 99%